Targeting the Microbiome: The Role of Low-FODMAP Diet in Modulating Gut Health for IBS and Inflammatory Conditions - Łukasz Mikołaj Karoń; Anna Zygmunt; Karolina Karoń; Daria Pedrycz; Grzegorz Drapała; Wojciech Grabowski; Emilia Pedrycz (Kazimierz Wielki University, 2024)
The Low-FODMAP diet has emerged as a key therapeutic intervention for managing irritable bowel syndrome (IBS), a prevalent gastrointestinal disorder characterized by recurrent abdominal pain and altered bowel habits. This study aims to evaluate the efficacy of the Low-FODMAP diet in alleviating IBS symptoms and to explore its potential as a broader therapeutic tool in other gastrointestinal disorders, including inflammatory conditions. Our review highlights significant improvements in symptom relief, notably in reducing bloating, pain, and bowel irregularities, which are commonly associated with IBS. The Low-FODMAP diet's mechanisms of action, involving modulation of gut microbiota and reduction of osmotic effects, provide new insights into its impact on gastrointestinal health.Our findings underscore the Low-FODMAP diet's potential applications beyond IBS, suggesting benefits in conditions such as inflammatory bowel disease (IBD) and small intestinal bacterial overgrowth (SIBO). However, the long-term impacts of this diet on gut microbiota composition, mental health, and immune function require further investigation. Future research should focus on these aspects, especially in relation to diet sustainability and microbial diversity. The clinical implications of this study encourage healthcare providers to consider the Low-FODMAP diet as a personalized, non-pharmacological option for gastrointestinal symptom management, with careful monitoring to ensure nutritional adequacy and individual patient needs.